Is government really solving the housing problem? - Monsod, Toby C. (2011)
Informal housing arrangements, substandard structures, congestion, and land-use conflicts characterize the urban housing problem in the Philippines. The record suggests that the response of the state, especially its reliance on below- market-priced mortgage loans, has aggravated the situation. If the housing problem is to be solved, government needs to rethink its role in housing finance, delink housing social assistance from finance markets, and turn its attention to fundamental supply side and urban governance issues.
Keywords: Housing; Housing policy; Housing finance